Four new species of Georissa W. Blanford, 1864 (Gastropoda, Hydrocenidae) from Thailand - Kanyaporn Klongklaew; Supattra Poeaim; Pongrat Dumrongrojwattana (Zoosystematics and Evolution, 2024)
Hydrocenid snails have received little research attention compared to other land snail groups, arguably due to their small size. The present study examines the diversity of hydrocenid snails in limestone hills in central, eastern and southern Thailand. Four new species of Georissa W. Blanford, 1864 are described: G. quinquelirata sp. nov. from central Thailand, G. sagitta sp. nov. and G. kohsichangensis sp. nov. from eastern Thailand, and G. digitinota sp. nov. from southern Thailand. These four new species are distinguished by unique characteristics in their shell, including protoconch sculpture and shell shape, operculum, and radula morphology. A phylogenetic analysis of mitochondrial DNA sequences confirms the distinctiveness of all four species.
Keywords: Aquatic Invertebrate Ecology and Behavior; Mollusks and Parasites Studies; Marine Biology and Ecology Research